Sandbox Policy: Crypto Asset Expansion Setting Efforts - Syauket, Amalia (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2022)
Crypto Asset Trading is Growing Rapidly in Recent Years. Throughout January-May 2021, Crypto Asset Users managed to grow more than 50%, from around 4 million people last year, to 6.5 million people today. Likewise, if viewed from the side of the value of crypto assets in Indonesia, which swelled to Rp. 370 trillion. That number rose five times compared to the previous year, which was recorded at only Rp. 65 trillion. The Increase in Investors in the Digital Asset Commodity Business is Due to the Digitalization of the Economy. This Research Uses Qualitative-Normative Research Methods By Reviewing And Describing Library Materials Relevant To Sandbox Policy To Find Out How The Regulatory Model Is Specifically Regarding Crypto Investments, an investment that is relatively new and requires protection so that people feel safe and comfortable doing so. crypto investment. This study results show that the Government uses sandbox policy modeling to accommodate changes in responding to the necessity of disruption and fundamental innovation in dealing with the growth of crypto assets in the country, with a sandbox policy where crypto trading is allowed to continue, at the same time regulations will be corrected, by guaranteeing confidentiality. As well as transactions, so that people will be protected in making crypto investments.   Keywords: sandbox policy, crypto currency as a commodity, the role of Bappeti